The Cooperation of Vocational High Schools and Industries in Achieving Graduates Competence - Nahriana Nahriana; Anas Arfandi (Universitas Negeri Makassar, 2020)
This study aimed to examine the relationships among synergistic cooperation between vocational schools and industries in the implementation of the apprenticeship program. It observed from support for industrial facilities (X1), technical guidance (X2), and the quality of graduates (Y) of culinary vocational school in Makassar, either directly or indirectly through the of competencies (X3). The study conducted at a culinary vocational school with a sample of 107 students. The data collected by using questionnaires, documentation, and interviews. It analyzed by quantitative descriptive analysis and path analysis. The results of the study concluded that: (1) cooperation synergies contribute simultaneously toward the mastery of competencies, and (2) industrial facilities support, technical guidance and competence provide simultaneously and significantly toward the quality of graduates